The Genomics of Circadian Timing in a Wild Bird, the Great Tit (Parus major) - Laine, Veronika N.; Atema, Els; Vlaming, Priscilla; Verhagen, Irene; Mateman, Christa; Ramakers, Jip J. C.; van Oers, Kees; Spoelstra, Kamiel; Visser, Marcel E. (Frontiers in Ecology and Evolution, 2019)
Circadian rhythms are ubiquitous among taxa and are essential for coping with recurrent daily events, leading to selection on the properties of the clock underlying these rhythms. To quantify this selection in the wild, we need, however, to phenotype wild individuals, which is difficult using the standard laboratory approach for which individuals need to be kept under constant conditions. To overcome this problem, we explored the possibility to link the variation in a key clock property, circadian period (Tau), to genetic variation. We measured Tau in 152 captive great tits (Parus major). We further linked Tau to two circadian phase markers, the onset of activity in the Light:Dark cycle, and the first onset in constant conditions (Dim:Dim), directly after entrainment. We did a genome-wide association study using a 650k SNP chip, and we linked genetic polymorphisms of a set of twelve candidate genes, to Tau and the two circadian phase markers. In line with earlier studies, Tau was heritable (h2 =0.48 ± 0.22). Despite this genetic variation, we did not find any significant associations at the genome-wide level with the measured traits and only one candidate gene showed association with onset of activity in the Light:Dark cycle. Identifying the genetic base of circadian timing for wild species thus remains challenging. Including alternative molecular methods such as epigenetics or transcriptomics could help to unravel the molecular basis of the biological clock in great tits.